THE EFFECT CREATIVE LEADERSHIP IN THE INNOVATIVE CLIMATE: LEADER DIALECTICAL THINKING AS A MODERATING VARIABLE - Liqaa Mutter Atti; Mustafa Salah Gumer; Krar Muhsin Thajil (Journal Park Publishing, 2023)
The climate that encourages innovation represents an important strategic dimension for which active organizations seek as it is the optimal mechanism for their development. To achieve this purpose, organizations need creative leadership that allows them to enjoy high professionalism to carry out their basic duties and tasks. To try to identify the modified role of the dialectic leader's thinking. The study included a sample of 354 employees in the South Refineries Company who were chosen randomly. The researchers used the questionnaire in order to reach the objectives of this study by formulating hypotheses that test that relationship, and we reached a set of results that indicate the existence of a positive role for creative leadership in the innovative climate. Also, this effect will be greater when the leader's dialectical thinking is at a high level. These results were discussed in order to identify one of the important mechanisms for managing human capital in industrial organizations in the oil sector.
Keywords: Creative leadership; Innovative climate; leader dialectical thinking; Employees